Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1088/0031-9155/50/14/012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 2D ion chamber array for the verification of radiotherapy treatments

Abstract: In this study we investigated the characteristics of a commercial ion chamber array and its performance in the verification of radiotherapy plans. The device was the 2D Array Seven29 model (PTW, Freiburg, Germany). This is a two-dimensional detector array with 729 ionization chambers uniformly arranged in a 27 x 27 matrix with an active area of 27 x 27 cm(2). The detector short-, medium- and long-term reproducibility have been tested through an extensive set of repeated measurements. Short-term reproducibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
139
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(149 citation statements)
references
References 24 publications
(20 reference statements)
7
139
0
3
Order By: Relevance
“…The PTW 2D Array seven29 has 729 ionization chambers in a 10 mm pitch 27×27 array. Spezi et al (15) reported the successful application of this detector to radiation therapy and verified the performance. The sensitive volume of a unit chamber is 5 mm×5 mm×5 mm and the ionization chambers of the array are open to the air.…”
Section: Methodsmentioning
confidence: 86%
“…The PTW 2D Array seven29 has 729 ionization chambers in a 10 mm pitch 27×27 array. Spezi et al (15) reported the successful application of this detector to radiation therapy and verified the performance. The sensitive volume of a unit chamber is 5 mm×5 mm×5 mm and the ionization chambers of the array are open to the air.…”
Section: Methodsmentioning
confidence: 86%
“…The following work shows that this limitation can be solved by taking into account the fact that partial coverage of a volumetric detector by a radiation beam gives a response proportional to the irradiated volume, as described by Yang et al ( 8 ) Spezi et al ( 9 ) studied the response of a 2D ion chamber array when radiation fields gradually increase the coverage of the detector area, and found a close correspondence between detector coverage and its response.…”
Section: Introductionmentioning
confidence: 89%
“…Several authors have studied the sensitivity and reproducibility parameters of this array and the results obtained are comparable with similar, commonly used detectors. ( 7 , 9 ) The VeriSoft software (PTW‐Freiburg, Germany) was used to record radiation dose readings. The array was optically aligned with the MLC so that each leaf corresponded to one row of detectors.…”
Section: Methodsmentioning
confidence: 99%
“…Accuracy of treatment delivery of complex treatment plans is assured through a quality assurance (QA) process using ion chambers, films and more commonly with diode array,1, 2 and ion chamber array measurements 3. Measured data are generally compared against planned data using two‐dimensional (2‐D) gamma analysis.…”
Section: Introductionmentioning
confidence: 99%